Most bothersome symptoms in patients with migraine: A hospital‐based study in Taiwan. Issue 5 (25th April 2022) - Tu, Yi‐Hsien; Wang, Yen‐Feng; Yuan, Hsiangkuo; Chen, Shih‐Pin; Tzeng, Yi‐Shiang; Chen, Wei‐Ta; Lai, Kuan‐Lin; Ling, Yu‐Hsiang; Wang, Shuu‐Jiun
Abstract: Objective: To investigate the distribution, clinical associations, and treatment responses for the most bothersome symptoms of migraine in a large sample of patients with migraine in Taiwan. Background: The most bothersome symptom is recently recommended as a co‐primary endpoint in clinical trials of acute treatment of migraine. However, most clinical trials and observational studies have been conducted in the United States and Europe, with photophobia representing the most common most bothersome symptom. Methods: Patients who were newly diagnosed with migraine by headache specialists in Taipei Veterans General Hospital were recruited. All participants completed a questionnaire for headache profile, including the most bothersome symptom. Clinical associations of the most bothersome symptoms and response rates to previous acute treatments were analyzed. Results: Among the recruited 1188 patients with migraine (female 79.4%, mean age 39.0 ± 12.1 years) in this cross‐sectional study, nausea ( n  = 729/1188, 61.4%) was the most common symptom that was most bothersome, followed by phonophobia ( n  = 280/1188, 23.6%), and photophobia ( n  = 122/1188, 10.3%). The frequency ranking was the same regardless of sex and age. Compared to migraine without aura, migraine with aura was associated with photophobia (adjusted odds ratio [OR] = 2.97, 95% confidence interval [CI] 1.76–5.0, p  < 0.001). Chronic migraine was associated with phonophobia (adjusted OR = 1.51, 95% CI 1.13–2.01, p  = 0.005), but there was a lower chance for nausea (adjusted OR = 0.68, 95% CI 0.53–0.88, p  = 0.004), as the most bothersome symptom. Patients with different most‐bothersome symptoms responded similarly to previous acute treatments, with an overall response rate of 52.2% ( n  = 550/1053). Conclusion: Patients with migraine in Taiwan reported a distinct ranking of the most bothersome symptom. However, the response rates of the most bothersome symptom and headache were similar, which supports the most bothersome symptom as an outcome measure for acute treatment of migraine. Further studies recruiting different populations are required to investigate regional differences in most bothersome symptoms.